2012
DOI: 10.1161/circgenetics.111.961037
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Targeted Analysis of Copy Number Variants Identifies 3 Novel Associations With Coronary Heart Disease Traits

Abstract: Background— Copy number variants (CNVs) are a major form of genomic variation, which may be implicated in complex disease phenotypes. However, investigation of the role of CNVs in coronary heart disease (CHD) traits has been limited. Methods and Results— We examined the use of the cnvHap algorithm for CNV detection, using data for 2500 men from the Second Northwick Park Heart Study (NPHS-II). An Illumina custom chip, including 722 single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This might be caused by variations in other genes such as APOC3 and PNPLA5 (Jorgensen et al 2014, Lange et al 2014). Furthermore, CNVs also play a crucial role in FH for unique cases (Myocardial Infarction Genetics, Kathiresan, et al 2009, Costelloe et al 2012). Considering the serious phenotype of proband F11, we believe that genetic factors may have had a dominant effect.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This might be caused by variations in other genes such as APOC3 and PNPLA5 (Jorgensen et al 2014, Lange et al 2014). Furthermore, CNVs also play a crucial role in FH for unique cases (Myocardial Infarction Genetics, Kathiresan, et al 2009, Costelloe et al 2012). Considering the serious phenotype of proband F11, we believe that genetic factors may have had a dominant effect.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…For example, APOB mutations may cause the least severe phenotype of the three (Soutar and Naoumova 2007). Besides LDLR , APOB and PCSK9 mutations, some copy number variants (CNVs) (Myocardial Infarction Genetics, Kathiresan et al 2009; Costelloe et al 2012) and rare mutations in associated genes, such as LDLRAP1 (Maglio et al 2014), PNPLA5 (Lange et al 2014) and APOC3 (Jorgensen et al 2014) have also been reported in FH patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional basis for these associations requires further substantiation. 23 Hospital Percutaneous Coronary Intervention Appropriateness and In-Hospital Procedural Outcomes: Insights From the NCDR Summary: Measuring PCI quality has traditionally focused on processes of care and postprocedural outcomes, such as in-hospital mortality, bleeding and vascular complication rates, and provision of guideline-recommended medications. PCI appropriateness is increasingly being incorporated into registries and quality improvement programs to measure the quality of patient selection for PCI, although the relationship to traditional PCI quality metrics is unknown.…”
Section: Gene-targeted Analysis Of Copy Number Variants Identifies 3 mentioning
confidence: 99%
“…The studies of CNVs in coronary artery disease have typically used DNA isolated from peripheral blood, and inconclusive results were obtained891011. The most pronounced genomic imbalance in patients with coronary artery disease and metabolic comorbidity are possibly detected in the target disease organs, such as coronary arteries.…”
mentioning
confidence: 99%